2011
DOI: 10.3174/ajnr.a2352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correlations of Brain Lesion Distribution in Multiple Sclerosis: An Exploratory Study

Abstract: BACKGROUND AND PURPOSE:In MS, the total brain lesion volume and spatial distribution of lesions across the brain vary widely among individual patients. We hypothesized that spatial distribution may be partially driven by genetic predisposition, and we aimed to explore relations among candidate genes and the spatial distribution of white matter brain lesions in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A recent larger study with 126 people with RRMS and 42 with SPMS has found that phenotypes associated with a higher total brain lesion volume were also associated with an increased local lesion probability. 26 This study has a number of limitations that are worth noting. First, including lesion load as a covariate in the model yielded no areas of significance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent larger study with 126 people with RRMS and 42 with SPMS has found that phenotypes associated with a higher total brain lesion volume were also associated with an increased local lesion probability. 26 This study has a number of limitations that are worth noting. First, including lesion load as a covariate in the model yielded no areas of significance.…”
Section: Discussionmentioning
confidence: 96%
“…A recent larger study with 126 people with RRMS and 42 with SPMS has found that phenotypes associated with a higher total brain lesion volume were also associated with an increased local lesion probability. 26…”
Section: Discussionmentioning
confidence: 99%
“…In all analyses, age and sex were used as covariates. In addition, since it is not clear whether the total brain LV can be relevant to lesion frequency assessment [23], [25], [26], all analyses were repeated adding T2-LV as a covariate. Values of T2-LV were log-transformed in order to obtain a normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-analyses have revealed that monitoring CNS damage using MRI is a poor predictor of disease progression in MS, likely because variation in the resulting damage (shape, location, size) obscures its consequence [ 51 , 52 ]. Clinically, MRI quantification of lesion load weakly correlates with immune responses (0.1 < ρ < 0.6) [ 53 , 54 ] and future disability (0.1 < ρ < 0.5) [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%